Ni una menos : the conceptualization of femicides on facebook - Piñero, Rocío Belén (2017)
The present study analyzes the conceptual frames of the phenomenon “femicide” underlying Facebook interactions. This study brings together Critical Discourse Studies (2008), Cognitive Semantics (Cienki, 2007; Dancygier & Sweetser, 2014; Fillmore, 2006; Minsky, 1975; Ziem, 2014) and Gender Studies (Bourdieu, 2001; Cabrera Ullivarri, 2011; Segato, 2010; Warner, 1994). The corpus consists of a “polylogue” (Bou-Franch, 2013) made up of forty nine responses that appeared in the public Facebook event “Ni Una Menos Córdoba”, which invited to massive demonstrations on June 3rd, 2015 in Argentina.